A Review Towards Selective Cobalt Recovery in Solvent Extraction: Potential of Ionic Liquids as Diluents and Extractants - Romero-Figueroa, J; Quijada-Maldonado, E; Olea-Chandia, F (Elsevier B.V., 2024)
Cobalt (Co) stands out as one of the most critical metals in contemporary use, particularly due to its increasing demand in technological products and especially in electromobility. Over the years, ionic liquids (ILs) have provided a green alternative to volatile organic solvents in hydrometallurgy due to their outstanding properties, such as the negligible vapor pressure and their increased selectivity provided in separation processes, which opens the possibility to ramp up the Co-production while maintaining sustainable mining processes. Thus, this review offers a complete comprehensive and critical summary of published works on the use of ILs in the hydrometallurgy of Co, starting from the leaching from a primary source by conventional methods and then, from the pregnant leach solution (PLS) focuses on the advantages and disadvantages of solvent extraction (SX) in different aqueous media (chlorinated, nitrated, and sulfated) in which ILs are used to separate selectively Co from a multi-metal mixture. In the following section, its recovery from the loaded organic phase by acid stripping is discussed. Finally, this review provides the challenges that ILs should overcome to be viable for large-scale industrial applications and the opportunities that exhibit for selective recovery of Co from PLS capitalizing. © 2024 Elsevier B.V.